Complete early regression of asymptomatic hindbrain herniation caused by minor head trauma. Issue 2 (25th February 2019) - Ble, Christina; Tsitsopoulos, Parmenion P; Sidiropoulou, Maria; Karakouti, Anna; Tsonidis, Christos
Abstract: Very few cases of cerebellar tonsillar herniation resulting from head trauma have previously been reported. We present a case of an 11-month-old girl who suffered a minor head trauma. Computed tomography (CT) scan of the head showed an occipital bone fracture and blood in the fourth ventricle. Magnetic resonance imaging (MRI) scan of the brain 2 days later revealed cerebellar edema and displacement of the cerebellar tonsils 6 mm below the foramen magnum. She was discharged from the hospital without neurological deficits. Repeat brain MRI scan, 1 month after trauma, demonstrated complete regression of the hindbrain herniation. During the hospital stay and at follow-up, no symptoms and signs related to posterior fossa involvement were noted.